The impact of return on assets (ROA), current ratio (CR), debt to assets ratio (DAR), and company size on effective tax rate (ETR) for the top 100 companies in Kompas in the years 2020-2023 - Febe, Margareta; Novianti, Bella; Theotista, Giovanny (JAAF (Journal of Applied Accounting and Finance), 2024)
This study aims to examine the impact of various financial circumstances on the effective tax rate (ETR) of manufacturing enterprises listed on the Indonesia Stock Exchange between 2020 and 2023. The sample size was 47 distinct industrial organizations, and a panel data regression analysis is implemented to achieve the investigation's objectives. The return on assets (ROA) and the debt-to-asset ratio (DAR) are both significant components in the process of determining the effective tax rate (ETR), as established by the research that was examined. Despite this, it is crucial to recognize that the efficiency transfer rate (ETR) does not seem to be significantly impacted by the current ratio (CR). It is recommended that organizations analyse the financial factors that affect the effective tax burden they are subjected to. The following findings serve as the foundation for this recommendation.